2017
DOI: 10.5152/npa.2017.18091
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre Syndrome and its Variants: Clinical Course and Prognostic Factors

Abstract: Introduction: We aimed to analyze the frequency, clinical characteristics, medical treatment options and final functional status of Guillain-Barré syndrome (GBS) and its variants in a population from a tertiary hospital setting. Methods: All medical records of patients with acute inflammatory polyneuropathy between the years of 1998-2013 were retrospectively screened. Demographic, clinical and laboratory information, treatment options and the rate of recovery of the patients were gathered. Results: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
2
1
2
Order By: Relevance
“…Comparing our findings with other studies conducted in Turkey, one study 17 reported an average length of stay in the rehabilitation clinic as 33.5 ± 4.9 days (range: 4-77 days), while another study 18 reported a longer duration of 86.4 ± 13.2 days. The time from disease onset to admission to the rehabilitation clinic for adult patients in our study was 21.29 ± 12 days, which aligns with the existing literature 17 - 19 .…”
Section: Discussionsupporting
confidence: 91%
“…Comparing our findings with other studies conducted in Turkey, one study 17 reported an average length of stay in the rehabilitation clinic as 33.5 ± 4.9 days (range: 4-77 days), while another study 18 reported a longer duration of 86.4 ± 13.2 days. The time from disease onset to admission to the rehabilitation clinic for adult patients in our study was 21.29 ± 12 days, which aligns with the existing literature 17 - 19 .…”
Section: Discussionsupporting
confidence: 91%
“…[7][8][9] Studies from Turkey that were conducted in western regions demonstrated that AIDP was also the most frequent type of GBS. 18,20 Compared to these reports, axonal subtypes were more common in our study results. Our study, to the best of our knowledge, is the first study investigated the prevalence of GBS subtypes in an Eastern region of Turkey, but our results are consistent with a previous study from the same region that found higher rates of AMAN subtypes in their study population that included pediatric patients mostly.…”
Section: Discussioncontrasting
confidence: 76%
“…The spring was the most common season the patients presented as reported in a recent study from western region of Turkey but the rate of onset during the fall in our study was much more common than this report. 18 Overall, these variabilities in subtypes, type of infection and onset of season might be due to epidemiological, and geographical differences between western and eastern regions of the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В отечественной и зарубежной литературе большое внимание уделено вопросу восстановления после СГБ [9][10][11][12][13][14][15][16][17][18]. Доказанными прогностически неблагоприятными факторами восстановления являются: возраст старше 60 лет, предшествующая развитию неврологической симптоматики диарея, быстрое прогрессирование заболевания в фазу нарастания симптоматики (фульминантное развитие до плегии в первые 7 сут), выраженность двигательных нарушений в остром периоде, необходимость в искусственной вентиляции легких, наличие антител к ганглиозидам периферических нервов, а также аксональная форма заболевания [19][20][21][22][23][24][25].…”
Section: Introductionunclassified